Cold adaptation of the Antarctic haloarchaea Halohasta litchfieldiae and Halorubrum lacusprofundi - Williams, TJ; Liao, Y; Ye, J; Kuchel, RP; Poljak, A; Raftery, MJ; Cavicchioli, R (Environmental Microbiology, 2017)
Halohasta litchfieldiae represents ∼ 44% and Halorubrum lacusprofundi ∼ 10% of the hypersaline, perennially cold (≥ −20°C) Deep Lake community in Antarctica. We used proteomics and microscopy to define physiological responses of these haloarchaea to growth at high (30°C) and low (10 and 4°C) temperatures. The proteomic data indicate that both species responded to low temperature by modifying their cell envelope including protein N-glycosylation, maintaining osmotic balance and translation initiation, and modifying RNA turnover and tRNA modification. Distinctions between the two species included DNA protection and repair strategies (e.g. roles of UspA and Rad50), and metabolism of glycerol and pyruvate. For Hrr. lacusprofundi, low temperature led to the formation of polyhydroxyalkanoate-like granules, with granule formation occurring by an unknown mechanism. Hrr. lacusprofundi also formed biofilms and synthesized high levels of Hsp20 chaperones. Hht. litchfieldiae was characterized by an active CRISPR system, and elevated levels of the core gene expression machinery, which contrasted markedly to the decreased levels of Hrr. lacusprofundi. These findings greatly expand the understanding of cellular mechanisms of cold adaptation in psychrophilic archaea, and provide insight into how Hht. litchfieldiae gains dominance in Deep Lake.